Strategies for screening, occupational prevention, and management of COVID-19 in outpatient clinics in Shandong - Zhang, Yan; Lu, Yan; Tang, Juan; Sun, Yu; Zhao, Ze-Hua; Jian, Xiang-Dong; Gao, Xi-Mei (Frontiers in Public Health, 2022)
Objective We hope to analyze the information of outpatients in a tertiary care hospital during the epidemic of COVID-19, so as to formulate effective regulations for the prevention and control of COVID-19. Methods We collected information from outpatients from January 28, 2020 to March 2, 2020 and performed the statistical analysis. Results During the study period, there were more than 60,000 outpatients. Among them, 404 patients with a body temperature above 37.3°C who had not been to Wuhan and had no contact with people from Wuhan. There were 8 people who had contact with people from Wuhan, such as 4 people with fever, 3 people with normal body temperature but cough symptoms, and 1 person with normal body temperature and no other discomfort. There were 2 patients with high body temperature from the epidemic area in Wuhan, and one novel Coronavirus patient was confirmed as the final result. Conclusion During the COVID-19 pandemic, outpatient medical staff should enhance their awareness of protection, hospitals should standardize the outpatient COVID-19 prevention and control system, improve the prevention and emergency system, and reduce occupational exposure hazards and the occurrence of post-exposure infections.